Helical poly(phenyl isocyanide)s grafted selectively on C-6 of cellulose for improved chiral recognition ability. (1st March 2020) - Qian, Hao; Shen, Xiaofei; Huang, Hailong; Zhang, Yan; Zhang, Mingtao; Wang, Huiqing; Wang, Zhongkai
Highlights: Selectively grafting PPI onto C-6 of Cellulose to retain cellulose's 3D structure. Cell-6-PPIn were prepared by alkyne-azide cycloaddition "click" chemistry. Cell-6-PPIn showed right-handed helicity with 96.6 % improved CD intensity. Cell-6-PPIn exhibited better chiral recognition to L-Phe-DNSP than PPIn alone. Cellulose backbone was a new way for promoting helix for artificial helical polymer. Abstract: Cellulose graft copolymers are an effective way to endow new properties to cellulose substrate, as well the rigidity, regularity, and helicity of the cellulose backbone could induce the self-assembly of supramolecular structures. In this work, right-handed helical poly(phenyl isocyanide)s (PPIn ) were grafted selectively onto C-6-cellulose. Alkyne-terminated PPIn was synthesized by living polymerization of right-handed phenyl isocyanide monomer using an alkyne-terminated palladium(II) complex as an initiator/catalyst, and were grafted onto the C-6 of the cellulose backbone (Cell-6-g-PPIn ) at various chain lengths using copper-catalyzed alkyne-azide cycloaddition (CuAAC) "click" chemistry. We confirmed the successful grafting by liquid 1 H NMR and 13 C NMR, as well as solid 13 C NMR, FTIR, and GPC. After grafting onto cellulose, the right-handed chirality of PPIn was significantly increased by 111.2%. Additionally, the Cell-6-g-PPIn exhibited better chiral recognition of L-Phe-DNSP than PPIn alone. Therefore, the helical cellulose backbone has enhanced effect on preferred helix of PPIn .